A FEMINIST STYLISTICS ANALYSIS IN TAYLOR SWIFT’S SONG “THE MAN” - AZURA DHARMAYA; SHANAZ MUTIA; RAHMADSYAH RANGKUTI (LINGUISTICA, 2024)
Feminist stylistic analysis of song lyrics can reveal how gender and power relations are represented in music. This research uses observation methods in collecting data by note-taking techniques. The analysis of transitivity choices using Halliday's systemic functional grammar theory can provide a deeper perspective on the relationship between language structure and meaning in the context of feminist song lyrics. The song aims to talk about a strong feminist message, permeating the narrative of gender inequality in society. The highlight of the song which is also the key reason for the stigma and stereotypes that arise in the society was found through the technique of portraying women's experience and their comparison with men's experiences in the community and because this through the desire to "be a man" the song wants to convey the message of gender equality.